Identification of dynamic U-values for supply-air double windows based on experiments - Huang, Yujian; El Mankibi, Mohamed; Cantin, Richard (CLIMA 2022 conference, 2022)
The double windows with supply-air are recommended for both new and retrofitted buildings where preheating fresh air is needed especially when dealing with historical and protected buildings. To evaluate their energy saving potentials in buildings and optimize their performance, building energy simulations are necessary. In building energy simulation tools, the thermal transmittance (i.e., U-value) is one of the most important input parameters. The conventional U-value is a static indicator and a number of numerical studies have been proposed to identify U-value with varying window parameters. However, there is still a lack of laboratory experimental studies to get accurate U-value and evaluate numerical modelling results. Moreover, the performances of supply-air windows are related with environmental parameters and thus the use of conventional U-value might lead to a significant deviation between the simulated building energy and the real one. The purpose of this study is to provide dynamic U-values which could be varied according to environmental conditions. Firstly, an adapted guarded hot box is set up and it is calibrated by controlling air velocities and air temperatures in both cold and hot sides. Secondly, the U-values of supply-air windows are measured with varying environmental parameters and window parameters. Thirdly, the regression analysis is applied to describe the correlation between U-values and the influential factors, and thus one can easily evaluate U-value under different environment conditions. A future work is to integrate the regression correlation with energy simulation tools to have a comprehensive exploration of supply-air windows in different climate regions.